Impact of body weight on intervertebral disc: a finite element analysis of lumbar spine total disc replacement / Siti Nurfaezah Zahari ... [et al.] - Zahari, Siti Nurfaezah; Abd Latif, Mohd Juzaila; Zakaria, Mohamad Shukri; Akiah, Masni Azian; Nguyen, Ho Quang; Abdul Kadir, Mohammed Rafiq (UiTM Press, 2025)
Total disc replacement is a frequently performed surgical intervention for managing severe degenerative disc disease, aiming to maintain lumbar spine mobility. Nevertheless, long-term outcomes have highlighted concerns such as spinal instability and degeneration of adjacent segments. This study explores the biomechanical implications of body weight on adjacent vertebral segments in a lumbar spine implanted with a total disc replacement prosthesis through finite element analysis. Detailed three-dimensional lumbar spine finite element models were developed, including both an intact spine and a spine with the Maverick prosthesis implanted at the L4-L5 segment, with verification against existing literature. The models underwent follower compression loads of 500 N, 800 N, and 1200 N, representing normal, overweight, and obese conditions, combined with pure moments of 7.5 Nm applied in flexion and extension. The analysis presented that increased body weight and the rigid characteristics of the Maverick prosthesis at the L4-L5 significantly influenced segmental motion, nucleus pulposus pressure, and annulus fibrosus stress compared to intact lumbar spine. The increasing body weight affected lumbar spine segmental motion, with the implanted lumbar spine model showing altered intersegmental rotation by 57% during extension motion. Additionally, notable increases in nucleus pulposus pressure and annulus fibrosus stress were observed, reaching 155% and 124% respectively, at the L3-L4 segment during extension under obese conditions. These biomechanical changes may contribute to early intervertebral disc damage and annular tear at the disc rim.